Time Domain and Qualitative Analysis of a Compact Asymmetrically Fed Circular UWB Antenna for WBAN Scenarios - P, Venkatesh; T V, Narmadha; M, Ponnrajakumari; K, Lavanya (International Journal of Electrical and Computer Engineering Systems, 2024)
This article presents about the design, time domain analysis and qualitative analysis of a circular monopole Ultra Wideband (UWB) antenna for Wireless Body Area Networks (WBAN) applications. The size of the proposed antenna is 30 x 30 x 1 mm3. The proposed antenna provides Ultra wide bandwidth from 2 – 10 GHz and also complies with IEEE C95.3 safety standards. The simulated and measured results are close to each other with minimum deviations. To ensure proper and less distorted communication in real time scenarios, time domain analysis was done for free space, on body and off body conditions. The magnitude and phase of transmission coefficient (S21) were found to be consistent. The group delay was analyzed under free space, on &off body conditions whose variations are less than 0.5 ns in the entire UWB range. Fidelity factor was also analyzed for flat and bent conditions to ensure pulse similarity. Also to ensure the communication link quality, the obtained minimum path loss of 51.10 dB and maximum Received Signal Power of 0.17 dBm were found to be satisfactory warranting a good transmission and reception characteristics of the proposed antenna.